Thionated perylene diimides with intense absorbance in the near-IR - Llewellyn, Ben A.; Davies, Stephen E.; Pfeiffer, Constance R.; Cooper, Mick; Lewis, William; Champness, Neil R. (Royal Society of Chemistry, 2015)
A synthetic strategy involving a combination of tetra-thionation and amine substitution in the bay region of a perylene diimide (PDI) leads to remarkable examples of neutral PDIs with intense absorption maxima in the near infrared. Generation of the corresponding monoanions red shifts the absorption profile to give short-wavelength infrared bands.